2022
DOI: 10.1038/s41586-022-05453-y
|View full text |Cite
|
Sign up to set email alerts
|

A 2-million-year-old ecosystem in Greenland uncovered by environmental DNA

Abstract: Late Pliocene and Early Pleistocene epochs 3.6 to 0.8 million years ago1 had climates resembling those forecasted under future warming2. Palaeoclimatic records show strong polar amplification with mean annual temperatures of 11–19 °C above contemporary values3,4. The biological communities inhabiting the Arctic during this time remain poorly known because fossils are rare5. Here we report an ancient environmental DNA6 (eDNA) record describing the rich plant and animal assemblages of the Kap København Formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 89 publications
2
131
0
Order By: Relevance
“…We recently recovered DNA from sediments dated to 2.4 Ma where the thermal age predicted no DNA survival. 12 Additionally, that study showed that the amount of DNA sediment adsorbs and retains depends on its mineralogic composition. In this communication, the term preservation is considered a function of DNA stabilization offered by the substrate (degree of immobilization and binding capacity) as well as resistance to biological, chemical and thermal degradation of the mineral-bound DNA.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…We recently recovered DNA from sediments dated to 2.4 Ma where the thermal age predicted no DNA survival. 12 Additionally, that study showed that the amount of DNA sediment adsorbs and retains depends on its mineralogic composition. In this communication, the term preservation is considered a function of DNA stabilization offered by the substrate (degree of immobilization and binding capacity) as well as resistance to biological, chemical and thermal degradation of the mineral-bound DNA.…”
Section: Introductionmentioning
confidence: 95%
“…Different surfaces will interact with DNA in different ways, depending on their composition and surface charge. For example, clay minerals, which adsorb an order of magnitude more DNA compared to other minerals, 12 are composed of layers of silica tetrahedra (T) and layers of magnesium or aluminum octahedra (O) (Fig. 1A)).…”
Section: Overview Of Interfacial Geochemical Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 However, advances made in the field of sedimentary ancient DNA (SedaDNA) underlines that, DNA can be preserved for at least 2 Ma years, and the adsorption of the DNA to mineral surfaces are argued to be key for the preservation. 8 In principle, all sedimentary minerals all hold a potential to adsorb some amount of extracellular DNA. Currently there is about 0.45 Gt of extracellular DNA associated with sediments in the top 10 cm of the ocean floor, and more than 90% of that DNA extracellular.…”
Section: Introductionmentioning
confidence: 99%